1997
DOI: 10.1128/jcm.35.7.1800-1804.1997
|View full text |Cite
|
Sign up to set email alerts
|

The role of arbitrarily primed PCR in identifying the source of an outbreak of Legionnaires' disease

Abstract: An outbreak of community-acquired Legionnaires' disease (LD) occurred in Providence, R.I., in fall 1993. To find the outbreak source, exposures of 17 case patients were compared to those of 33 matched controls. Case patients were more likely than controls to have visited a section of downtown (area A) during the 2 weeks before illness (11 [65%] versus 9 [27%]; matched odds ratio, 6.5; P ‫؍‬ 0.01). Water samples were cultured from 27 aerosol-producing devices within area A. Legionella pneumophila serogroup 1 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…5). The PFGE profile was similar to a published profile from isolates of an outbreak that had occurred in Providence, Rhode Island, in 1993 [5,9]. Subsequent re-testing by one laboratory of all isolates confirmed that strains isolated from the Rhode Island outbreak were indeed indistinguishable, by each subtyping method, from the strain that caused this outbreak (Fig.…”
Section: Environmental Investigationsupporting
confidence: 69%
See 1 more Smart Citation
“…5). The PFGE profile was similar to a published profile from isolates of an outbreak that had occurred in Providence, Rhode Island, in 1993 [5,9]. Subsequent re-testing by one laboratory of all isolates confirmed that strains isolated from the Rhode Island outbreak were indeed indistinguishable, by each subtyping method, from the strain that caused this outbreak (Fig.…”
Section: Environmental Investigationsupporting
confidence: 69%
“…Molecular subtyping was useful in our outbreak investigation because it distinguished clinical outbreak isolates from clinical isolates of patients in other areas of the County. However, multiple DNA fingerprinting techniques could not distinguish isolates of two cooling towers from each other, from the outbreak strain, and even from an unrelated Legionnaires' disease outbreak that occurred in 1993 in Rhode Island [5,9]. This implies that this subtype may be common in the United States or that the subtyping techniques were insufficiently discriminating for this strain.…”
Section: Discussionmentioning
confidence: 95%
“…Various molecular methods based on genomic DNA polymorphisms of L. pneumophila serogroup 1 can be used to discriminate between epidemic and nonepidemic isolates (9,10,13,14,16,18,21,22,(25)(26)(27). The finding that 25 sporadic clinical L. pneumophila isolates from the Paris area had identical AP-PCR patterns led us to suspect that the method lacked discriminatory power.…”
Section: Discussionmentioning
confidence: 99%
“…The respective advantages and limits of the different epidemiologic markers used in this investigation have been discussed in detail elsewhere [14]. Overall, AP‐PCR—which was found to be rapid, easy to perform, cost‐effective and discriminative—appears to be the method of choice for analyzing strains of Legionella involved in nosocomial infections [14,16].…”
Section: Discussionmentioning
confidence: 99%
“…A number of typing methods have already been proposed for comparing strains of Legionella. They include monoclonal antibody (MAb) typing [9,11,12], plasmid profiles [4], DNA restriction patterns [3,9], ribotyping [12,13], pulsed‐field gel electrophoresis [10,13], and various PCR fingerprinting methods [12,14–16].…”
Section: Introductionmentioning
confidence: 99%